The experience of pregnant women with HIV: scoping review - A.A. Putri Melastini; Mufdlilah Mufdlilah (Journal of Health Technology Assessment in Midwifery, 2021)
HIV attacks human immune system and HIV occurrence during pregnancy is four times higher compared to when not pregnant. ANC visit can help early detection and identify if there is complication related to the mother’s health and the infant’s health. The purpose of this study was the evidence of pregnant women’s experience with HIV. Data sources used databses i.e. Pubmed, Wiley, Science Direct, and Google Scholar. There were 714,336 articles from initial hit publised from 2011-2020, and after filtering process 8 articles were included. This scoping review method was adapted from Arksey and O’Malley. There were 3 themes emerged from this study, which were psychology, coping stress, and the role of medical staffs. Studies stated that participants experience lack of comfortable circumstances, not obtaining sufficient attention and experience violence in the household.